Development of a Hydroxypropyl-β-Cyclodextrin-Based Liquid Formulation for the Oral Administration of Propranolol in Pediatric Therapy - Marzia Cirri; Paola Mura; Simona Benedetti; Susanna Buratti (MDPI AG, 2023)
Propranolol (PPN) is widely used in children to treat various cardiovascular diseases. The availability of a suitable PPN solution should avoid recourse to extemporaneous preparations of unknown/limited stability, as commonly made in hospital pharmacies. However, the development of pediatric PPN solutions is hindered by their instability to light and stability at pH ≈ 3, bitter taste, and the need to improve palatability and avoid co-solvents, flavoring agents, or preservatives that are potentially toxic. In this study, cyclodextrin (CD) complexation has been exploited to develop a safe, stable, and palatable oral pediatric solution of PPN. An initial screening among various CDs allowed us to select HPβCD for its good complexing ability and no toxicity. Drug-HPβCD physical mixtures or co-ground systems (1:1 or 1:2 mol:mol) were used to prepare 0.2% w/v drug solutions. Photo stability studies evidenced the protective effect of HPβCD, revealing a reduction of up to 75% in the drug degradation rate after 1 h of exposure to UV radiation. Storage stability studies showed unchanged physical-chemical properties and almost constant drug concentration after 6 months and under accelerated conditions (40 °C), despite the less aggressive pH (≈5.5) of the solution. The electronic tongue test proved that the HPβCD taste-masking properties improved the formulation palatability, with a 30% reduction in drug bitterness.